2007
DOI: 10.1210/en.2007-0038
|View full text |Cite
|
Sign up to set email alerts
|

VGF-Derived Peptide, TLQP-21, Regulates Food Intake and Body Weight in Siberian Hamsters

Abstract: The Siberian hamster survives winter by decreasing food intake and catabolizing abdominal fat reserves, resulting in a sustained, profound loss of body weight. VGF gene expression is photoperiodically regulated in the hypothalamus with significantly higher expression in lean Siberian hamsters. The aim of this study was to investigate the role of VGF in regulating these seasonal cycles by determining the effects of a VGF-derived peptide (TLQP-21) on food intake and body weight. Acute intracerebroventricular adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
100
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 81 publications
(109 citation statements)
references
References 45 publications
(69 reference statements)
8
100
1
Order By: Relevance
“…This study confirms our previous report [7] but partially contrasts the findings by Jethwa et al [37] who showed that daily icv injection of TLQP-21 exerted a catabolic effect in the Siberian hamster which was associated with decreased body and WAT weight and was dependent on reduced food intake but not on increased energy expenditure. Therefore, three independent studies [7,37]; present study) evidence a catabolic role for TLQP-21, but differ in the possible mechanism underlying the effect observed: (1) increased energy expenditure/WAT catabolic effects in our studies; (2) reduced food intake in the hamster studies. A number of methodological (repeated injections vs. chronic infusion; the dose used etc.)…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…This study confirms our previous report [7] but partially contrasts the findings by Jethwa et al [37] who showed that daily icv injection of TLQP-21 exerted a catabolic effect in the Siberian hamster which was associated with decreased body and WAT weight and was dependent on reduced food intake but not on increased energy expenditure. Therefore, three independent studies [7,37]; present study) evidence a catabolic role for TLQP-21, but differ in the possible mechanism underlying the effect observed: (1) increased energy expenditure/WAT catabolic effects in our studies; (2) reduced food intake in the hamster studies. A number of methodological (repeated injections vs. chronic infusion; the dose used etc.)…”
Section: Discussionsupporting
confidence: 91%
“…The lack of increase in adipose tissue is the more likely explanation for hormonal findings, i.e., the lack of increase in leptin and the decrease in ghrelin, which were evident instead in HFD-aCSF mice [47,56,69]. This study confirms our previous report [7] but partially contrasts the findings by Jethwa et al [37] who showed that daily icv injection of TLQP-21 exerted a catabolic effect in the Siberian hamster which was associated with decreased body and WAT weight and was dependent on reduced food intake but not on increased energy expenditure. Therefore, three independent studies [7,37]; present study) evidence a catabolic role for TLQP-21, but differ in the possible mechanism underlying the effect observed: (1) increased energy expenditure/WAT catabolic effects in our studies; (2) reduced food intake in the hamster studies.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations